Impact of Long-Term Dual Antiplatelet Therapy on Immature Platelet Count and Platelet Reactivity. (July 2018) - Verdoia, Monica; Pergolini, Patrizia; Rolla, Roberta; Barbieri, Lucia; Schaffer, Alon; Marino, Paolo; Bellomo, Giorgio; Suryapranata, Harry; De Luca, Giuseppe
The immature platelet count (IPC) is a potential marker of platelet reactivity. We assessed the relationship between IPC during chronic dual antiplatelet therapy (DAPT) and the response to antiplatelet drugs (acetylsalycilic acid + clopidogrel/ticagrelor). We included 286 patients: 167 (58.4%) patients received ticagrelor and 119 (41.6%) received clopidogrel. At a median follow-up of 46.5 days, the variation in IPC displayed an absolute median (interquartile range [IQR]) of −11.9 × 10 3 /µL (−182.7 to 160.8), corresponding to a median percentage change in IPC ([%ΔIPC] IQR) of −0.3% (−21.9% to 35.5%), with an increase in IPC levels in those on ticagrelor and a decrease in IPC levels in those on clopidogrel. We observed an inverse association of lower platelet reactivity at different tests and a higher increase in IPC ( r = −0.14, P = .04 for arachidonic acid test; r = −0.12, P = .05 for collagen test; and r = −0.13, P = .02 for adenosine diphosphate test [ADP]). The rate of poor effectiveness of ADP antagonists was the only independent predictor of a ΔIPC above the third tertile (odds ratio [95% confidence interval] = 0.55 [0.32-0.99]; P = .048). We showed that in patients treated with chronic DAPT, an increase in IPC is significantly related to lower levels of platelet reactivity.